2016
DOI: 10.1183/13993003.01157-2015
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in lung cancer: a world ofEGFR

Abstract: Epidermal growth factor receptor gene (EGFR) mutation status has emerged as a crucial issue in lung cancer management. Availability and cost of tests and tyrosine kinase inhibitors (TKIs) may vary as a function of country development.We conducted a prospective specialist opinion survey to map EGFR test and EGFR-TKI availability and detect associations with the Human Development Index (HDI). A questionnaire was sent to specialists in thoracic oncology in all United Nations Member States.We obtained responses fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…In the present issue of European Respiratory Journal, CARBONNAUX et al [9] highlight two major financial issues, namely, as expected, cost in terms of access to the drug but primarily the cost in terms of access to molecular testing. Almost 10 years after the identification of the EGFR mutation [6,7], inequalities in the availability of the EGFR mutation test exist worldwide.…”
mentioning
confidence: 88%
See 4 more Smart Citations
“…In the present issue of European Respiratory Journal, CARBONNAUX et al [9] highlight two major financial issues, namely, as expected, cost in terms of access to the drug but primarily the cost in terms of access to molecular testing. Almost 10 years after the identification of the EGFR mutation [6,7], inequalities in the availability of the EGFR mutation test exist worldwide.…”
mentioning
confidence: 88%
“…However, in a recent study, 50% of Asian patients with EGFR mutations were not female non-smokers [17]. Interestingly, CARBONNAUX et al [9] reported higher EGFR mutation positivity in Hispanic populations (30% in Mexico and 25% in Colombia) compared with Caucasian population (∼11%) [4]. Of note, although tobacco consumption has been related to molecular abnormalities (such as KRAS or STK11 mutations [18,19]), there are no aetiological findings that explain the occurrence of somatic EGFR mutations.…”
mentioning
confidence: 91%
See 3 more Smart Citations